Leadership Style and Principal Supervision in Improving Teacher Performance at State High Schools in Kutai Kartanegara Regency, East Kalimantan Province, Indonesia - Warman Warman; Soerjo Adi Poernomo; Syafrudin Januar; Lorensius Amon (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study examines the leadership style and supervision of principals in improving teacher performance in several public high schools in Kutai Kartanegara Regency, East Kalimantan Province. This study uses a qualitative approach with a cross-sectional descriptive method. Observation and interview techniques were used to obtain data. The collected data were analyzed in the form of data reduction, data presentation, and conclusion drawing, as well as checking the validity of the data using observation and triangulation. The results of this study indicate that the principals' leadership style in improving teacher performance is a leadership style democratic and authoritarian. Authoritarian style is done through observation timeliness of attendance of teachers in schools and teaching time in the classroom. The democratic style is carried out by providing opportunities for teachers to attend training according to the needs of the school and the needs of teachers. The Teaching supervision program principal's oriented towards the guidance of teachers' tasks, such as preparing teaching programs and preparing learning tools. Obstacles in the supervision of principals are the low competence of most supervisors, activities outside the supervision schedule, and difficulty changing old habits.